Dinamika Komunikasi Antar Pasangan: Dynamics of Communication Between Couples - Fitra Yeni (Fakultas Keperawatan Universitas Andalas, 2013)
Communication is a someone ability to express their feeling and an ability to understanding others. Communication and intimacy are related, because communication is a key of intimacy. Lack of skills to communicate each other in spouse will take a great deal to cause a maarriege conflict. Marriage conflict can effect a divorce. This study use phenomonology study. The participants in this study are man and his spouse who have children. The result of this study showed that the participants have their own style in communication with their spouse. A men have no problem in communication with thwir spouse, but in the other side, women showed the disappointed expression in communication with their spouse because the differentiation in background. The participants have their own effort in order to have an understanding meaning each other, such as build the interaction, have a same perception, give the rewards and punishment, talk fluently, anger, and courious. The participants tell that communication can affect the development of family postively and negatively.